2006
DOI: 10.1016/j.ydbio.2006.08.074
|View full text |Cite
|
Sign up to set email alerts
|

The sea urchin kinome: A first look

Abstract: This paper reports a preliminary in silico analysis of the sea urchin kinome. The predicted protein kinases in the sea urchin genome were identified, annotated and classified, according to both function and kinase domain taxonomy. The results show that the sea urchin kinome, consisting of 353 protein kinases, is closer to the Drosophila kinome (239) than the human kinome (518) with respect to total kinase number. However, the diversity of sea urchin kinases is surprisingly similar to humans, since the urchin k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 94 publications
3
69
0
Order By: Relevance
“…PKC represents a large family of enzymes with at least 10 isoforms (Mellor and Parker, 1998). In the sea urchin, four different PKC genes have been found in the recently released Strongylocentrotes purpuratus genome (Bradham et al, 2006). The PKC inhibitors, as well as the antibodies used herein, can act (or react) on several mammalian PKC isoforms, and not necessarily with the same potency on each isoform.…”
Section: Discussionmentioning
confidence: 99%
“…PKC represents a large family of enzymes with at least 10 isoforms (Mellor and Parker, 1998). In the sea urchin, four different PKC genes have been found in the recently released Strongylocentrotes purpuratus genome (Bradham et al, 2006). The PKC inhibitors, as well as the antibodies used herein, can act (or react) on several mammalian PKC isoforms, and not necessarily with the same potency on each isoform.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an S. mansoni Syk-family PTK, TK4, has been identified that may play a role in germ cell development (Knobloch et al 2002). The importance of PTKs to schistosome development is not surprising given that these signalling enzymes regulate multiple physiological processes, including differentiation, in animals; indeed, the importance of protein kinases to development is highlighted by the recent finding that 85 % of sea urchin signalling kinases are expressed in the developing embryo (Bradham et al 2006). Genistein blocks the activity of multiple PTKs in S. mansoni miracidia (as demonstrated here by p-Tyr-100 blotting) so the effects observed in the present work are unlikely specific to a single PTK.…”
Section: Bmentioning
confidence: 99%
“…Polo-like kinases (Plks) are found in all eukaryotes and are characterized by a highly conserved kinase domain and one or two C-terminal polo box domains (PBDs). These include the Plk1 subfamily, containing Drosophila polo and mammalian Plk1; the SAK subfamily, containing Drosophila SAK and mammalian Plk4, both of which are widely distributed across the eukaryotes; and the Plk2 subfamily, containing vertebrate Plk2 and Plk3 and also including homologs from echinoderms (4,8,10,35). The PBD participates in subcellular localization and partner interaction (16,54).…”
mentioning
confidence: 99%